2016
DOI: 10.1016/j.atherosclerosis.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin E1 attenuates atherosclerosis in absence of cholesterol-lowering effects and on top of atorvastatin

Abstract: RvE1 attenuates atherogenesis both alone and on top of a statin. The local effects of RvE1 are demonstrated by the modulated aortic expression of genes involved in inflammatory and immune responses, without altering plasma cholesterol or circulating SAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 41 publications
(57 reference statements)
5
58
0
Order By: Relevance
“…In summary, we have demonstrated that RvE1 attenuates neointima formation in response to injury through the suppression of inflammatory reactions and VSMC migration. Given that RvE1 confers multiple protective effects in an atherosclerosis setting (72,73) as well as myocardial recovery from ischemia and reperfusion (24,74), EPA supplementation or RvE1 itself may serve as a viable agent for the future prevention of in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have demonstrated that RvE1 attenuates neointima formation in response to injury through the suppression of inflammatory reactions and VSMC migration. Given that RvE1 confers multiple protective effects in an atherosclerosis setting (72,73) as well as myocardial recovery from ischemia and reperfusion (24,74), EPA supplementation or RvE1 itself may serve as a viable agent for the future prevention of in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, CCR-5 has been reported to be involved in atherosclerosis. Increased monocyte CCR-5 expression is associated with atherosclerosis, and statins therapy has been demonstrated to reduce CCR-5 concentrations (51,52). Furthermore, CCR-5 expression in monocytes has been demonstrated to be important for migration during the development of atherosclerosis (53) and the CCR5 antagonist, maraviroc, has been shown to be effective in limiting plaque progression in different atherosclerosis animal models (54).…”
Section: Discussionmentioning
confidence: 99%
“…19 Similarly, 12/15 lipoxygenase, the enzyme responsible for the synthesis of Lipoxin A4, RvD1, and MaR1 was also shown to be protective toward atherosclerosis, 20 setting the stage for the indication that progression of atherosclerosis may be a consequence of failed resolution. 21 Given the associative evidence for atheroprotective effects of the precursors of resolving lipid mediators, and more recently of Resolvin E1 in ApoE*3Leiden mice, 22 we here hypothesized that atheroprogression may partly be explained by an imbalance of the arterial lipid mediator profile. Therefore, we set to investigate how the balance of these mediators changes during the course of atherosclerosis, aiming at identifying relevant resolution-inducing candidates.…”
mentioning
confidence: 99%